The Driving Factors for the Rise of African Student Migration to Russia - Y. A. Mohammed; M. B. Denisenko (Moscow Polytechnic University, 2024)
This study investigates the factors that drive African students to Russia. The number of African students studying in Russia from the 2010/11 to 2022/2023 academic year increased more than fivefold: from 6.7 thousand to 34.4 thousand. The paper was based on an online survey provided to African students between February and November 2023. A sample of 275 African students from 28 countries was used. Findings revealed that the major factors that draw African students to Russia are the quality of education and the quality of life. We compared the quality of education between both genders along with the quality of life. The findings also revealed that females are more interested in the quality of life than males, while males are more interested in the quality of education than females. The findings suggested that policymakers should consider age and previous education as major variables in student migration.